Broader conceptualization of remission assessed by the remission from depression questionnaire and its association with symptomatic remission: a prospective, multicenter, observational study. Issue 1 (December 2016) - Montoya, Alonso; Lebrec, Jeremie; Keane, Karen; Fregenal, Irene; Ciudad, Antonio; Moríñigo, Ángel; Agüera-Ortiz, Luis; Romera, Irene; Gilaberte, Inmaculada; Zimmerman, Mark
Abstract Background Goals of treating major depressive disorder (MDD) include achieving remission and avoiding relapse. It is possible that patients may have a broader view of remission than what is captured via clinician-rated scales. This patient perspective may, in turn, have an impact on treatment outcomes. Methods The association between a broader conceptualization of remission, based on the Remission from Depression Questionnaire (RDQ) score at baseline, and being in symptomatic remission after 6 months was evaluated in subjects (N  = 613) with MDD in symptomatic remission at baseline (17-item Hamilton Rating Scale for Depression [HAMD-17] ≤7). Specific aspects of depression were assessed from physician and patient perspectives as secondary endpoints. A backwards selection strategy was used to statistically model remission status and determine association of factors with potential to influence remission. Results At month 6, after adjustment for baseline HAMD-17 score, there was no association between baseline RDQ score and symptomatic remission status (HAMD-17), relapse, composite remission status, healthcare resource utilization, or quality of life. There was no association between functional impairment scores at baseline (Sheehan Disability Scale and Social and Occupational Functioning Assessment Scale) and symptomatic remission status (HAMD-17) at month 6. Conclusions This study indicates that RDQ-constructs are independent from symptomatic remission. Symptom severity at study entry appeared to be the only significant predictor of eventual relapse during the 6-month follow-up period. However, our results also suggest that the current definition of remission that is based on symptom reduction should be further elaborated and that alternative or additional definitions should be considered in determining remission.